Exploration of image-based stimuli to assess mental toughness among medical students of Universiti Sains Malaysia - Nordin, Nadia Izzati (2023)
Mental toughness (MT) is a psychological construct comprised of cognitive, emotional, and behavioural processes that explain an individual’s capacity to cope with stress and predicts optimal performance in adversity. Apart from psychological-based studies, researchers have been shifting to physiological and neuroscience research to advance the knowledge and understanding of mental toughness. These studies require non-invasive modulation of emotion, stress, and cognitive effort induction. This present study seeks to explore a set of image-based stimuli to assess mental toughness among medical students. The study design consisted of four phases. Phase I involved the validation of the MTQ-48 questionnaire. Phase II involved the assessment of mental toughness, depression, anxiety, and stress in medical students. Phase III involved the selection of 156 image-based stimuli from databases such as the International Affective Picture System (IAPS), the Nencki Affective Picture System (NAPS), the Emotional Picture Set (EmoPics), the Open Affective Standardized Image Set (OASIS), the Geneva Affective Picture Database (GAPED), and online licensed no copyright platforms such as Pexels and PxHere. These images were then content validated by panel of experts according to academic related and clinical related medical context. The valence and arousal of normative evaluations were obtained by medical students using self-assessment manikin (SAM). Phase IV involved the evaluation of the stress intensity of the image-based stimuli from Phase III and its relationship with mental toughness, perceived stress, and stress score. Findings from factor analyses stated that MTQ-48 is unreliable for use in medical context as the fit indices do not meet acceptable standards. Consequently, MTQ-10 resulted from the validation process in Phase I had better model fit and used throughout the study. Besides, a significant inverse relationship was found between mental toughness and depression, anxiety, and stress. Out of 156 images, only 149 images were relevant to academic and clinical related medical context and were obtained valence and arousal mean value for each image. 36 images with negative valence were used to evaluate the stress intensity of the images and its relationship with mental toughness, perceived stress, and stress questionnaire. These findings provide evidence that the stress intensity of the set of image-based stimuli was 19% significantly predicted mental toughness, 43.9 % predicted perceived stress and 19.8% predicted stress. Hence, the set of image-based stimuli possibly to be used to assess mental toughness, perceived stress, and stress along with other variables in future research to facilitate a greater understanding of the affective processes associated with mental toughness in medical students.